2015
DOI: 10.1245/s10434-015-4781-z
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Inflammation-Associated Blood Cell Markers in Patients with Upper Tract Urothelial Carcinoma

Abstract: RDW and WBC count have the advantage of their common accessibility and are useful markers to predict outcome of UTUC in the preoperative setting. RDW and WBC count could provide additional prognostic value and help physicians identify patients at high risk for mortality and formulate individualized treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…After removed duplicate and irrelevant papers, a total of 16 articles were included in this analysis. For case ascertainment, fifteen articles [1327] performed retrospective analysis (3953 participants), and one article [28] had both a retrospective design and a prospectively design in two independent patients population (314 participants). Therefore, a total of 16 articles including 17 studies with 4267 patients were included in this analysis with a median sample size of 179 (from 81 to 938).…”
Section: Resultsmentioning
confidence: 99%
“…After removed duplicate and irrelevant papers, a total of 16 articles were included in this analysis. For case ascertainment, fifteen articles [1327] performed retrospective analysis (3953 participants), and one article [28] had both a retrospective design and a prospectively design in two independent patients population (314 participants). Therefore, a total of 16 articles including 17 studies with 4267 patients were included in this analysis with a median sample size of 179 (from 81 to 938).…”
Section: Resultsmentioning
confidence: 99%
“…In relation to this limitation, the platelet cutoff value was arbitrarily set to the median value (234 × 10 9 /L) in order to maximize the statistical power of the analyses. In this context, a recent study of UTUC used a similar cutoff value (230 × 10 9 /L), although other studies have indicated that thrombocytosis (>400 × 10 9 /L) was associated with adverse clinicopathological features and a poor prognosis in cases of UTUC or urinary bladder UC . However, this cutoff value was not realistic in the present study, as only a few patients had both PD‐L1 positivity and a platelet count of >400 × 10 9 /L.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this limitation, the platelet cutoff value was arbitrarily set to the median value (234 × 10 9 /L) in order to maximize the statistical power of the analyses. In this context, a recent study of UTUC used a similar cutoff value (230 × 10 9 /L), 41 although other studies have indicated that thrombocytosis (>400 × 10 9 /L) was associated with The interaction was assessed using the Wald test and the cross-product of PD-L1 and platelet count (as a continuous variable) in the Cox model.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the comments by Dr. Zeng on our published article. 1 First, patients with high red blood cell distribution width (RDW) had significantly lower body mass index than those with low RDW (22.96 ± 3.64 vs. 24.31 ± 3.74, P = 0.015) in our derivation cohort. However, some previous studies indicated that obesity was associated with high RDW.…”
Section: To the Editorsmentioning
confidence: 86%